2020
DOI: 10.3390/diagnostics10050288
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Lateral Flow Immunoassays

Abstract: A new generation of magnetic lateral flow immunoassays is emerging as powerful tool for diagnostics. They rely on the use of magnetic nanoparticles (MNP) as detecting label, replacing conventional gold or latex beads. MNPs can be sensed and quantified by means of external devices, allowing the development of immunochromatographic tests with a quantitative capability. Moreover, they have an added advantage because they can be used for immunomagnetic separation (IMS), with improvements in selectivity and sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 96 publications
(153 reference statements)
0
45
0
Order By: Relevance
“…This is possible due to the physical and chemical characteristics of magnetic nanoparticles, which can be detected by means of magnetometric sensors. Magnetic LFIAs have been reported to detect different important analytes in numerous fields [ 35 ]. Moreover, magnetic labels not only allow quantification, but they can also be employed for immunomagnetic separation enabling isolation and enrichment of analyte [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is possible due to the physical and chemical characteristics of magnetic nanoparticles, which can be detected by means of magnetometric sensors. Magnetic LFIAs have been reported to detect different important analytes in numerous fields [ 35 ]. Moreover, magnetic labels not only allow quantification, but they can also be employed for immunomagnetic separation enabling isolation and enrichment of analyte [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The conventional immunochromatographic tests are the basis of the actual serological and antigen tests used to monitor and diagnosis of COVID-19. In recent years, research in this field is giving rise to a new generation of LFIAs relying on MNPs, and it could be considered that magnetic LFIA are emerging as powerful tool for diagnostics [ 19 ]. In this direction, previous studies from this research group showed the successful development of these kind of tests for prostatic cancer antigen, exosomes and histamine [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral flow immunoassays (LFIA), also called immunochromatographic tests, have been established as POC tests in recent years due to the rapid, low-cost, simple detection [5]. They are the basis for the well-known pregnancy test, but they can be designed for different applications in biomedicine, toxicology, food, agriculture, and environmental fields [6,7]. They consist of a membrane of nitrocellulose, where bioreceptors are immobilized.…”
Section: Introductionmentioning
confidence: 99%